Relevance of Article 7 of the Universal Declaration of Human Rights to the Enforcement of Prisoners’ Human Rights in Correctional Institutions - Prasetia, Riky; Arifin, Tajul; Fauzia, Ine (Jurist-Diction, 2025)
The treatment of prisoners often still deviates from human rights standards. In fact, prisoners are entitled to the same protection before the law as the general public. The purpose of this study is to examine how Article 7 of the Universal Declaration of Human Rights affects the protection of human rights of prisoners in Correctional Institutions. This study applies a normative juridical approach and a descriptive method of analysis. Data were collected using literature study techniques, as well as using qualitative data analysis techniques. The results of the study show that there are still problems related to the fulfillment of prisoners' rights to equality before the law and non-discriminatory treatment in correctional institutions, making Article 7 of the Universal Declaration of Human Rights relevant to be implemented. Several regulations in Indonesia show that there is a strong legal basis to support the implementation of Article 7 of the declaration. The findings of this study imply the need for optimal enforcement and supervision in fulfilling human rights for prisoners